2021
DOI: 10.1061/(asce)ey.1943-7897.0000723
|View full text |Cite
|
Sign up to set email alerts
|

Atomization Mechanism of Internally Mixing Twin-Fluid Y-Jet Atomizer

Abstract: The atomization mechanism of the gas-liquid multiphase flow through internally mixing twin-fluid Yjet atomizer has been studied by examining both the internal and external flow patterns. Superheated steam and Light Fuel Oil (LFO) are used as working fluids. The flow is numerically modeled using the compressible Navier-Stokes equations; hybrid Large Eddy Simulation approach through Wall Modeled Large Eddy Simulations (WMLES) is used to resolve the turbulence with the Large Eddy Simulations, whereas the Prandtl … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
10
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 38 publications
(53 reference statements)
1
10
0
Order By: Relevance
“…Nazeer et al 21 the GLR. 22 Zhou et al 23 conducted an experimental study on a Y-jet nozzle and reported a better internal flow pattern by predicting the droplet size distribution according to the GLR. It is essential to consider the internal flow mechanism of the fluids since a twin-fluid nozzle has a two-phase flow.…”
Section: Introductionmentioning
confidence: 99%
“…Nazeer et al 21 the GLR. 22 Zhou et al 23 conducted an experimental study on a Y-jet nozzle and reported a better internal flow pattern by predicting the droplet size distribution according to the GLR. It is essential to consider the internal flow mechanism of the fluids since a twin-fluid nozzle has a two-phase flow.…”
Section: Introductionmentioning
confidence: 99%
“…In this case, the kinetic energy of the gas is transferred to the slowly moving liquid [13]. In twin fluid nozzles the air-to-liquid mass flow ratio (ALR) is used to characterize the energy input [18,19]. In contrast to PS nozzles, the process conditions of the atomization gas can be used to control the resulting spray droplet size independently from the liquid throughput.…”
Section: Introductionmentioning
confidence: 99%
“…In the IM configuration, a high-velocity gas and the liquid are mixed inside the nozzle before the discharge orifice [16,18]. In IM atomizers, energy is transferred from the gas to the liquid in form of shear stresses, which induces instabilities in the liquid stream leading to dispersion of the liquid [18,19,21].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations